The Role of Pesantren in Economic Empowerment of the Ummah: A Qualitative Descriptive Study in Indonesia - Hakim, Lukman; Zikrifah, Amelia; Rahma Melati, Tri; Tresnawati, Dewi; Karti, Karti; Kresnapatty, Duva (El-kahfi | Jurnal Ekonomi Islam, 2025)
Pesantren, or Islamic boarding schools, hold strategic potential in advancing the economic empowerment of Muslim communities in Indonesia, particularly in rural and underserved regions. This study investigates how pesantren contribute to the economy of the ummah through institutional business practices, student entrepreneurship incubation, and community integration. Employing a qualitative descriptive approach, data were collected from three pesantren in Java through in-depth interviews, observations, and document analysis. The findings reveal three major themes: (1) pesantren serve as localized economic actors by managing small-scale agribusinesses and cooperatives, although most lack formal business structures; (2) some pesantren have developed business incubator programs to train santri in entrepreneurship, though these remain informal and unsupported by structured curricula; and (3) strategies to enhance pesantren’s economic role include capacity building, stakeholder collaboration, digital transformation, and alignment with national policies. These findings are analyzed in light of Islamic economic principles, maqashid shariah, prophetic traditions, DSN MUI regulations, and scholarly perspectives on Islamic entrepreneurship. The study concludes that while pesantren have great potential as agents of economic empowerment, sustainable impact requires institutional reform, structured educational integration, and systemic policy support.